Global stability of linearizing control with a new robust nonlinear observer of the induction motor - Chenafa, Mohammed; Mansouri, Abdellah; Bouhenna, Abderrahmane; Etien, Eric; Belaidi, Abdelkader; Denai, Mouloud Azzedine (Zielona Góra: Uniwersytet Zielonogórski)
This paper mainly deals with the design of an advanced control law with an observer for a special class of nonlinear systems. We design an observer with a gain as a function of speed. We study the solution to the output feedback torque and rotor fluxtracking problem for an induction motor model given in the natural frame.
Keywords: nonlinear observer; linearizing control; induction motor; global stability